La lujuria perpetua - Mastretta, Angeles (autor) ((Las Armas de Venus))
Incluye relatos de Angeles Mastretta, Alberto Ruy Sánchez, Jorge Javier Romero, Guillermo Fadanelli, Rafael Pérez Gay, Rocío Barrionuevo, María Teresa Priego, Naief Yehya, Eliseo Alberto, Salomé Derreza y Gilberto Prado Galán.